OVEN PANGGANG SEBAGAI SOLUSI PENGOLAHAN IKAN HIGIENIS DAN RAMAH LINGKUNGAN - Martuti, Nana Kariada Tri; Rosidah, Rosidah; Saputro, Danang Dwi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
Fish is a perishable food product, so as to be able to maintain the required quality processing. Processing of roasting fish traditionally done by the fishermen and their families in the region Tambakrejo Village Tanjung Mas Semarang. Roasting fish done by grilled over coconut shell charcoal produces less hygienic products. In addition, the resulting smoke spread into the surrounding environment so that the impact on the health of the toaster and the surrounding community. Traditional way of production capacity of 1.5 Kg of fish once baked, so if grilling fish in large numbers takes a long time. Roasting fish with oven roasted made from galvanized plate is advantageous alternative fish processing and environmentally friendly. Oven roast made in the multilevel system (3 level) where each level can accommodate fish from 2 to 2.5 kg of fish slices.